All I have to do is dream? The role of aspirations in intergenerational mobility and well-being - Warn N. Lekfuangfu; Reto Odermatt (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
In this paper, we study the determinants and consequences of educational and occupational aspirations. Basing our enquiry on the British NCDS 1958 cohort data, we assess the importance of aspirations for social mobility above and beyond other established determinants. We document educational and occupational inequalities in young individuals' aspirations, whereby parental aspirations are a strong predictor of children's aspiration-levels. While we find a positive correlation between aspirations and later achievement, we also provide evidence for reduced well-being in adulthood if aspirations in adolescence were higher than actual achievements later in life.
Keywords: I21; I24; J62; O15; 330; Aspirations; intergenerational mobility; life satisfaction; longitudinal study; CAMSIS score; UK